Aflatoxins associated oxidative stress and immunological alterations are mitigated by dietary supplementation of Pichia kudriavzevii in broiler chicks. (December 2021) - Ali, Ashiq; Khatoon, Aisha; Saleemi, Muhammad Kashif; Abbas, Rao Zahid
Abstract: Mycotoxins are the secondary metabolites of certain toxigenic fungi which pose severe health stress in humans, animals and poultry. Certain biological agents and components are used to adsorb mycotoxins in poultry industry which provide promising results in this regard. Pichia kudriazevii (PK), a novel yeast, has the ability to enhance the immune status of poultry chicks. The present study was designed to investigate the ameliorative potential of PK against aflatoxins associated immunosuppression and oxidative stress in broiler chicks. 180-one day old broiler chicks were equally divided into six groups and given different combinations of aflatoxins (300 and 600 μg/kg) and PK (1 g/kg). Parameters studied were antibody response to sheep red blood cells, lymphoproliferative response to PHA-P; phagocytic response by carbon clearance assay system, total antioxidant capacity and total oxidant status of chicks. Results of this experiment confirmed the immunomodulation and antioxidant capacity of PK against 300 μg/kg aflatoxin level. However such amelioration was partial when PK was used with 600 μg/kg aflatoxins. Moreover, the exact ratio of aflatoxin: PK to cause such amelioration still needs to be investigated. Highlights: Mycotoxins are the products of some toxigenic fungi and aflatoxins are extremely toxic as far as poultry industry is concerned. Pichia kudriazevii (PK) is a novel yeast which has the ability to enhance the immune status of poultry chicks. This study was opted to investigate the ameliorative potential of PK against aflatoxins induced alterations in broiler chicks. Results of this study confirmed the ameliorative potential of PK against aflatoxin induced alterations in broiler chicks.